Milliarcsecond Astrometry for the Galilean Moons Using Stellar Occultations - Morgado, B. E.; Gomes-Júnior, A. R. [UNESP]; Braga-Ribas, F.; Vieira-Martins, R.; Desmars, J.; Lainey, V.; D'Aversa, E.; Dunham, D.; Moore, J.; Baillié, K.; Herald, D.; Assafin, M.; et al. (American Astronomical Society, 2022)
A stellar occultation occurs when a Solar System object passes in front of a star for an observer. This technique allows the sizes and shapes of the occulting body to be determined with kilometer precision. In addition, this technique constrains the occulting body's positions, albedos, densities, and so on. In the context of the Galilean moons, these events can provide their best ground-based astrometry, with uncertainties in the order of 1 mas ( 1/43 km at Jupiter's distance during opposition). We organized campaigns and successfully observed a stellar occultation by Io (JI) in 2021, one by Ganymede (JIII) in 2020, and one by Europa (JII) in 2019, with stations in North and South America. We also re-analyzed two previously published events: one by Europa in 2016 and another by Ganymede in 2017. We then fit the known 3D shape of the occulting satellite and determine its center of figure. This resulted in astrometric positions with uncertainties in the milliarcsecond level. The positions obtained from these stellar occultations can be used together with dynamical models to ensure highly accurate orbits of the Galilean moons. These orbits can help when planning future space probes aiming at the Jovian system, such as JUICE by ESA and Europa Clipper by NASA. They also allow more efficient planning of flyby maneuvers.